Theme and Rheme Analysis in The Poem of Anne Finch Countess of Winchelsea: A Nocturnal Reverie - I Gusti Ayu Vina Widiadnya Putri; I Gusti Ayu Agung Sintha Satwika; I Made Kevin Raditya (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2026)
This study analyses the use of theme and rhyme in the poem A Nocturnal Reverie by Anne Finch, Countess of Winchelsea. Using Systemic Functional Linguistics as a framework, the research examines the themes employed and their functions in conveying the poem's meaning and narrative flow. The study utilizes qualitative methods, analyzing the thematic structures in each clause of the 50-line poem. Findings reveal the prevalence of marked themes (21.52% of clauses), with topical, textual, and interpersonal themes identified. Simple and multiple themes are observed, along with marked and unmarked themes. Topical themes include participants, processes, and circumstances. Textual themes, primarily conjunctive, create logical links between clauses. No interpersonal themes were found. The analysis demonstrates how theme choices contribute to the poem's abstract imagery and ambiguous effects. Marked themes emphasize temporal settings and create contrast. The thematic patterns highlight the poem's narrative progression and the author's stylistic choices. This research provides insights into thematic structures in classical poetry, allowing comparison with modern literary works. The findings enhance understanding of how theme-rheme patterns shape poetic meaning and flow. This study contributes to the broader field of discourse analysis in literature by illuminating thematic devices in historical poetry.